The Correlation between Matrix Metalloproteinase-9 (MMP-9) Immunohistochemical Expression and Histopathological Subtypes of Basal Cell Carcinoma: A Correlation between Matrix Metalloproteinase-9 (MMP-9) Immunohistochemical Expression and Histopathological Subtypes of Basal Cell Carcinoma - Aisyah, Siti; Intan, T. Kemala; Alferraly, T. Ibnu; Betty, Betty; Soekimin, Soekimin; Laksmi, Lidya Imelda (Majalah Patologi Indonesia, 2024)
ABSTRACT Background Basal cell carcinoma (BCC) is a non-melanocytic skin cancer originating basal layer of the epidermis and/or hair follicles that shows an increasing global incidence. Disease growth is slow, rarely metastasizes but has the ability to invade and destroy deeper surrounding tissues. Low mortality, but high morbidity. Matrix metalloproteinases are enzymes that can degrade various extracellular matrix components. In skin, MMP-9 expression may be increased by prolonged ultraviolet exposure. UV radiation is one of the causes of BCC. Method Analytic study with a cross sectional approach on 40 surgical samples diagnosed as BCC and then performed with MMP-9 immunohistochemical staining. The data obtained were processed with statistical software and the relationship between the immunohistochemical expression of MMP-9 with histopathological subtypes of basal cell carcinoma was used the Somers'd statistical test. Results The expression of MMP-9 in the lower risk BCC group with the weakest expression was 37.5%, the most common nodular BCC subtype was 27.5%. The higher risk BCC group with the strongest expression was 20.0%, the most common infiltrating BCC was 17.5%. There was a significant relationship between the immunohistochemical expression of MMP-9 with histopathological subtypes of basal cell carcinoma, p value <0.0001 (p<0.05). Conclusion This study proves that there is a significant relationship between the expression of MMP-9 with histopathological subtypes of basal cell carcinoma, so it can be considered as an additional marker to predict the recurrence.